Finger Hold Guided Imagery Relaxation Techniques Can Reduce Dysmenorrhoea - Yunita Yunita; Ribkha Itha Idhayanti; Christin Hiyana Tunggadewi (Midwifery and Nursing Research, 2022)
Background: During menstruation, teenagers often experience pain, which is known as dysmenorrhea. In most cases, dysmenorrhea is very uncomfortable for adolescents in carrying out daily activities. So it is necessary to intervene in the form of relaxation techniques to reduce the scale of pain in the dysmenorrhoea. The relaxation technique taken is the finger grip relaxation technique. This study to determine the effect of finger hold guided imagery relaxation technique intervention to reducing primary dysmenorrheascale in adolescents. Methods: The type of this research is Quasy experimental One Group Pretest Posttest research design. The measurement instrument used is finger hold guided imagery relaxation SOP and observation sheet. a total sampling was applied with 33 respondents. Result: There is a significant effect of finger hold guided imagery relaxation technique intervention. This is evidenced by the results of the Wilcoxon test with p value < 0.05. Strenghtenend by the results of z count of -5.062 and z table -1.645, z count > z table. Conclusion: Finger hold guided relaxation technique imagery is recommended for teenagers who have dysmenorrhea